Respuesta :

Answer:

y = 3 and x = - 5

Step-by-step explanation:

(a)

[tex]\frac{5-7y}{2+4y}[/tex] = [tex]\frac{-8}{7}[/tex] ( cross- multiply )

- 8(2 + 4y) = 7(5 - 7y) ← distribute parenthesis on both sides

- 16 - 32y = 35 - 49y ( add 49y to both sides )

- 16 + 17y = 35 ( add 16 to both sides )

17y = 51 ( divide both sides by 17 )

y = 3

-----------------------------------------------

(b)

x + 7 - [tex]\frac{8x}{3}[/tex] = [tex]\frac{17}{6}[/tex] - [tex]\frac{5x}{2}[/tex]

Multiply through by 6 to clear the fractions

6x + 42 - 16x = 17 - 15x

42 - 10x = 17 - 15x ( add 15x to both sides )

42 + 5x = 17 ( subtract 42 from both sides )

5x = - 25 ( divide both sides by 5 )

x = - 5